Spectrum of Biopsy Proven Glomerular Disease in Children at Kanti Children’s Hospital - Khatun, N; Bista, KP; Mahaseth, C (Journal of Nepal Paediatric Society, 2015)
Introduction: Glomerular disease is one of the most common forms of renal disease and can have many different clinical presentations. However there is variation in the prevalence in the type of glomerular disease according to geographical location and race of population. The aim of the study was to find the overall distribution pattern of glomerular disease based on renal biopsies. Material and Methods: The medical records of all children who underwent kidney biopsy (n=29) between January 2012-june 2014 were analyzed. In this retrospective study we review children from Kanti Children’s Hospital, Nephrology Department. Demographic data including age, sex and indication of kidney biopsy as well as complication of the procedures were recorded. Result: A total number of thirty one biopsies were done. Two children were excluded from the study due to inadequate tissue and artifacts defects in preservative. The remaining twenty nine biopsies were included in the study and analyzed. Renal disease was found nearly equal in both male and female (51.72% vs. 48.27%).Mean age was 10.95±3.30 years. Maximum number of biopsies (75.86%) was performed between 10- 15 years. The most common indication of the kidney biopsy was nephrotic syndrome (steroid resistant nephrotic syndrome and steroid dependent nephrotic syndrome, 31.02% followed by lupus nephritis 27.58%.The most common glomerular disease were focal segmental glomerulosclerosis and lupus nephritis both contribute 27.58%. Among lupus nephritis class III was found more common (44.44%) in children. IgA nephropathy was also contribute (17.24%) in all glomerular disease. Regarding the kidney biopsy complication gross hematuria was observed in 6.89% of children which was self-limited. Conclusion: FSGS and lupus nephritis is becoming the most common glomerular disease in children attending the Kanti Children Hospital. IgA nephropathy was also contribute the glomerular disease in the children. J Nepal Paediatr Soc 2014;34(3):225-229 DOI: http://dx.doi.org/10.3126/jnps.v34i3.11162